2008
DOI: 10.1136/bjo.2008.148833
|View full text |Cite
|
Sign up to set email alerts
|

Fundus autofluorescence and Fourier-domain optical coherence tomography imaging of 10 and 20 millisecond Pascal retinal photocoagulation treatment

Abstract: We report the in vivo spatial localisation and clinical correlation of medium-pulse Pascal photocoagulation burns within outer retina and RPE, using high-resolution FD-OCT and AF. Ophthalmoscopically invisible and threshold Pascal burns may be accurately localised and mapped by AF and FD-OCT, with monitoring over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 17 publications
0
45
0
1
Order By: Relevance
“…Recent work using the Pascal laser at 10-20 ms has shown more localised laser burns within the outer retina, hence potentially less risk of nerve fibre layer damage. 15 Al-Hussainy et al 27 reported reduced pain responses using single-spot 20 ms compared with single-spot 100 ms pulse duration laser PRP in diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work using the Pascal laser at 10-20 ms has shown more localised laser burns within the outer retina, hence potentially less risk of nerve fibre layer damage. 15 Al-Hussainy et al 27 reported reduced pain responses using single-spot 20 ms compared with single-spot 100 ms pulse duration laser PRP in diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, the outer retina appears to be the main site of laser burn formation. 15 At longer pulse durations, laser burns may cause fibrotic reactions in animal models. 16 Blankenship 17 reported temporal thickening of the nerve fibre layer in the rabbit retina after experimental laser photocoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…This may result in fewer secondary complications including loss of visual field and other psychophysical parameters associated with function of second-and third-order retinal neurons, which are typically preserved. 13,14 It has been established that shorter pulse duration burns have a resultant smaller diameter footprint on the retina, both laterally and axially, than longer duration burns with calculated axial retinal injury of 70 mm for 10 ms burns contrasted with approximately 220 mm for a 100 ms burn. 13 Fundus auto fluorescence and Fourier-domain optical coherence tomography in patients undergoing diabetic laser photocoagulation with 10 and 20 ms patterned short-duration burns suggest that gradual retinal lesion enlargement or 'creep' does not occur with shorter burns and that there may actually be progressive shrinkage rather than enlargement of these burns over time.…”
Section: Laser Photocoagulationmentioning
confidence: 99%
“…There may also be preservation and/or remodelling of the outer retinal layers including filling in of initial defects in photoreceptors, presumably by sliding from adjacent areas in pre-clinical models for smaller-sized burns of 200 mm or less, that may favourably affect VEGF distribution in the retina and visual field loss. [14][15][16] …”
Section: Laser Photocoagulationmentioning
confidence: 99%
“…7 The FD-OCT features at 1 hr showed that individual 10 ms burns produced a vertical band of moderate and high reflectivity that occupies the outer nuclear layer, with extension from the inner highly reflective layer (HRL) through the outer plexiform layer. Along either side of these vertical bands, small vacuoles of low reflectivity were present.…”
mentioning
confidence: 99%